Um novo olhar para a matemática financeira no ensino médio - Tamião, Fabio Carlos Badanai (Universidade Federal de São Carlos, 2014)
The teaching of financial mathematics is of great importance in the basic education curriculum. The students are challenged all the time with everyday situations involving the concepts of interest, discounts, financing, among others. In this work, we present the idealization and implementation of a didactic sequence, grounded in the perspective of Didactic Engineering, targeting a significant learning of Financial Mathematics in High School, with contextualized problem situations, use of scientific calculator, spreadsheets and computer software.
Keywords: Matemática - estudo e ensino; Matemática financeira; Sequência didática; Recursos tecnológicos; Didactic sequence; Financial mathematics; Technological resources; CIENCIAS EXATAS E DA TERRA::MATEMATICA